Prospective Observational Study of Bisphosphonate-Related Osteonecrosis of the Jaw in Multiple Myeloma: Microbiota Profiling and Cytokine Expression - Badros, Ashraf Z.; Meddeb, Mariam; Weikel, Dianna; Philip, Sunita; Milliron, Todd; Lapidus, Rena; Hester, Lisa; Goloubeva, Olga; Meiller, Timothy F.; Mongodin, Emmanuel F. (Frontiers in Oncology, 2021)
Purpose: define incidence and risk factors of osteonecrosis of the jaw (ONJ) and explore oral microbial signatures and host immune response as reflected by cytokine changes in saliva and serum in multiple myeloma (MM) patients on bisphosphate (BP) therapy. Patients and Methods: a single center observational prospective study of MM patients (n=110) on > 2 years of BP, none had ONJ at enrollment. Patients were followed every 3 months for 18 months with clinical/dental examination and serial measurements of in-flammatory cytokines, bone turnover markers and angiogenic growth factors. Oral micro-biota was characterized by sequencing of 16S rRNA gene from saliva. Results: Over the study period 14 patients (13%) developed BRONJ, at a median of 5.7 years (95% CI: 1.9-12.0) from MM diagnosis. Chronic periodontal disease was the main clinically observed risk factor. Oral microbial profiling revealed lower bacterial rich-ness/diversity in BRONJ. Streptococcus intermedius, S. mutans and S. perioris were abundant in controls; S. sonstellatus and S anginosus were prevalent in BRONJ. In the saliva, at baseline patients who developed BRONJ had higher levels of MIP-1β; TNF-α and IL-6 compared to those without BRONJ, cytokine profile consistent with M-1 mac-rophage activation. In the serum, patients with BRONJ have significantly lower levels of TGF beta and VEGF over the study period. Conclusion: Periodontal disease associated with low microbial diversity and predomi-nance of invasive species with a proinflammatory cytokine profile leading to tissue dam-age and alteration of immunity seems to be the main culprit in pathogenesis of BRONJ.